The association of fever with transfusion‐associated circulatory overload. Issue 1 (21st December 2016) - Parmar, N.; Pendergrast, J.; Lieberman, L.; Lin, Y.; Callum, J.; Cserti‐Gazdewich, C.
Abstract : Background: Fever is described in transfusion‐associated circulatory overload (TACO), reflecting either comprehensive haemovigilance or an inflammatory pathobiology (such as congestion‐associated atheroma disruptions). Methods: Hospital haemovigilance data (1/1/2010–31/12/2012) were reviewed for TACO cases (frequency and mode of referral). TACO with or without fever (TACO+F/−F) was examined for its association with patient age (as a surrogate for atheroma burden) and product age (as a surrogate for storage‐related pyrogens). Fever in allergic transfusion reactions was also compared. Results: Of 972 reactions, 107 suspected cases of TACO (11%) were seen. TACO+F vs. TACO−F occurred in 42·1 vs. 57·9%, respectively. TACO+F cases were discovered in referrals to investigate either a fever (in 47·1%) or dyspnoea (in 52·9%). Among TACO+F cases, 24·4% had already been febrile, whereas 75·6% exhibited a new reaction‐associated fever. After excluding preexisting fevers, TACO+F occurred in 31·8% of TACO, compared with 8·2% of allergic reactions with fever, for an odds ratio of 5·2 (2·9–9·4 [95% CI]), P < 0·001. TACO+F/TACO−F showed no difference in median host age (69 vs. 64 years, P = 0·3), RBC age (22 days +F/−F, P = 0·9) or severity. Conclusion: Transfusion‐associated circulatory overload disproportionately exhibits fever compared with allergic reactions. However, TACO+F did not associate with patient or product age, nor reflect severity. To better understand TACO+F, the fever‐congestion sequence merits attention. Further study is needed to see whether TACO+F occurs as reproducibly elsewhere, and in association with atherosclerosis in a better characterized cohort.